2008
DOI: 10.1016/j.jhydrol.2007.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Permeability analysis in bisized porous media: Wall effect between particles of different size

Abstract: SummaryThe permeability of binary packings of glass beads with different size ratio -13.3, 20, and 26.7, was investigated. In the Kozeny-Carman equation, the dependence of the tortuosity s on the mixture porosity e(x D ) was described according to s = 1/e n for different volume fraction of large particles in the mixture, x D . Obtained data on packing permeability shows that the parameter n is a function of the volume fraction and particle size ratio, with values between 0.5 and 0.4. This can be explained by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…The discussion until now has confirmed that material particle size, material sorting and material geometry all significantly influence the hydraulic conductivity [50,[52][53][54]. In Fe 0 beds, in-situ generated iron hydroxides tend to cement initial particles and decrease both porosity and permeability.…”
Section: Permeability Lossmentioning
confidence: 90%
See 2 more Smart Citations
“…The discussion until now has confirmed that material particle size, material sorting and material geometry all significantly influence the hydraulic conductivity [50,[52][53][54]. In Fe 0 beds, in-situ generated iron hydroxides tend to cement initial particles and decrease both porosity and permeability.…”
Section: Permeability Lossmentioning
confidence: 90%
“…4) was essentially lower for ZVI1 than for ZVI10 and ZVI9. This behaviour is primarily attributed to the material sorting [50][51][52][53][54]. In fact, a packed bed of a better sorted granular material exhibits a greater permeability.…”
Section: Mb Discolorationmentioning
confidence: 99%
See 1 more Smart Citation
“…HDC separation mechanism. The cylindrical capillary has a radius R and u(r) represents the local velocity for a stream line at a radial position r. The solvent and the mobile phase was water, the column had dimensions 200 4.6 mm ID and was packed with a mixture of glass spheres (65% with diameter 5 μm and 35% with diameter 19 μm), the average particle size [35][36][37][38][39][40] being 9.6 μm, = 0.316 and, therefore, the average pore radius, R, being 1.478 μm. Pullulan is a flexible random coil exopolysaccharide [41] and the R g -Mw relationship is The packed bed reported in Fig.…”
Section: Separation Mechanismsmentioning
confidence: 99%
“…PHE passages containing cross-corrugated chevron-type plates are much more complex than the ducts studied by Kozicki et al (1966) due to the presence of a series of expansions and contractions (Edwards et al, 1974). As a result of this complexity, Edwards et al (1974) and Charre et al (2002) analysed the performance of chevron-type PHEs making use of the theory developed for granular beds (Broniarz-Press et al, 2007;Chhabra et al, 2001;Dias et al, , 2008. Delplace and Leuliet (1995) explored the applicability of Eq.…”
Section: Introductionmentioning
confidence: 99%